A pilot study of diet lifestyle on complete blood picture, elements, and biological profile in females - Felemban, Shifa; Fathi Hamouda, Asmaa (Trends in Immunotherapy, 2024)
Obesity, a prevalent global health issue, is characterized by elevated lipid levels, altered hematological parameters, inflammation, and other related symptoms. A biological profile and complete blood count (CBC) are essential tools for assessing overall health and detecting various dysfunctions, including anemia, infections, leukemia, and heart diseases. In obese patients of both sexes, a high white blood cell count is a reliable indicator of leukemia risk, coronary complications, and inflammation. Notably, dietary and lifestyle changes can significantly improve obesity-related conditions and hematological disorders. This study examines the effects of a six-month dietary program on anthropometric measurements, biological profiles, elemental composition, and complete blood counts in 43 obese females with white blood cell counts above the normal range. Participants underwent comprehensive hematological, biochemical, and anthropometric assessments at the beginning and end of the diet program. The findings revealed a significant weight loss and substantial improvements in laboratory parameters and blood profiles. These improvements are likely due to the nutrient composition of the diet program. The investigation confirmed that modifying dietary intake by reducing consumption of high-acidic foods, fast foods, animal-derived lipids, refined carbohydrates, red meats, and non-seasonal produce, in favor of a nutrient-dense regimen comprising fruits, vegetables (consumed raw or steamed), fish, poultry, and whole grains, resulted in significant enhancements in hematological indices and biological markers. These enhancements substantially surpassed baseline measurements for complete blood count and biological profiles. However, alterations in the elemental profile were not statistically significant. Further studies are being conducted to examine these outcomes with greater specificity. Ongoing research aims to further understand these effects according to personal medical history, age, and sex.